2008
DOI: 10.1099/mic.0.2007/010900-0
|View full text |Cite
|
Sign up to set email alerts
|

A mutant in one of two exbD loci of a TonB system in Flavobacterium psychrophilum shows attenuated virulence and confers protection against cold water disease

Abstract: Flavobacterium psychrophilum is a psychrotrophic fish-pathogenic bacterium that causes cold water disease (CWD) in salmonids. By means of Tn4351 mutagenesis a mutant named FP1033, deficient in growth on iron-depleted medium, was previously isolated. FP1033 recovered the parental phenotype in the presence of iron. The gene disrupted by the transposon in this mutant encoded a protein with similarity to ExbD proteins, which are members of the TonB complex system involved in iron uptake mediated by siderophores. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 50 publications
2
49
1
Order By: Relevance
“…To our knowledge, only two reports have previously described two ExbD proteins encoded within the same TonB cluster in other Gram-negative microorganisms (43,44). In both cases, it was found that only one of the two ExbD proteins was involved in iron uptake functions, an observation that contrasts with our results showing that both exbD products are required for iron acquisition.…”
Section: Discussioncontrasting
confidence: 57%
“…To our knowledge, only two reports have previously described two ExbD proteins encoded within the same TonB cluster in other Gram-negative microorganisms (43,44). In both cases, it was found that only one of the two ExbD proteins was involved in iron uptake functions, an observation that contrasts with our results showing that both exbD products are required for iron acquisition.…”
Section: Discussioncontrasting
confidence: 57%
“…Some bacteria have more than one tonB or tonB-like gene, and in all cases, the connection between TonB-ExbBD and iron acquisition, when examined, has been clear (1,4,10,29,39,58,59,64,93,97,121,126,139). But recently, it has become apparent that some bacteria that contain an OM and IM, including L. pneumophila, and species of Chlamydia, Chlamydophila, Coxiella, Ehrlichia, Francisella, and Rickettsia do not have TonB-ExbBD (29,74).…”
Section: Discussionmentioning
confidence: 99%
“…As an important component of the iron uptake system, several TonB-dependent receptors were reported to have relevance in pathogen pathogenicity (Alvarez et al 2008, Tauseef et al 2011. In a comparative study of Flavobacterium columnare strains with high and low virulence, Li et al (2010) identified 3 tdr genes in the high virulence strain but not in the low virulence strain.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of the Fe 3+ -siderophore complex triggers conformational change in the receptor, which induces the passage of the ligand (Braun 2006, Krewulak & Vogel 2011. As a result, TDRs are associated with bacterial pathogenicity in species such as Flavobacterium psychrophilum, Escherichia coli, Riemerella anatipestifer, and Neisseria meningitides (Alvarez et al 2008, Hagan & Mobley 2009, Tauseef et al 2011, Lu et al 2013. However, the potential importance of TDRs in pathogenic P. fluorescens remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%